The war on illegal drug production and trafficking : an economic evaluation of Plan Colombia (2008)
This paper provides a thorough economic evaluation of the anti-drug policies implemented in Colombia between 2000 and 2006 under the so-called Plan Colombia. The paper develops a game theory model of the war against illegal drugs in producer countries. We explicitly model illegal drug markets, which allows us to account for the feedback effects between policies and market outcomes that are potentially important when evaluating large scale policy interventions such as Plan Colombia. We calibrate the model using available data for the war on cocaine production and trafficking as well as outcomes from the cocaine markets. Using the results from the calibration we estimate important measures of the costs, effectiveness, and efficiency of the war on drugs in Colombia. Finally we assess the impact of increases in the U.S. budget allocated to Plan Colombia, and find that a three-fold increase in the U.S. budget allocated to the war on drugs in Colombia would decrease the amount of cocaine reaching consumer countries by about 15%.